Female Sex Workers' Experiences Selling Sex during Pregnancy and Post‐Delivery in South Africa. Issue 3 (17th April 2019) - Parmley, Lauren; Rao, Amrita; Young, Katherine; Kose, Zamakayise; Phaswana‐Mafuya, Nancy; Mcingana, Mfezi; Lambert, Andy; Hausler, Harry; Baral, Stefan; Schwartz, Sheree
Abstract: Nearly 75 percent of female sex workers (FSWs) in Port Elizabeth, South Africa are mothers, many of whom engage in sex work during pregnancy or after delivery. We conducted in‐depth interviews with 22 postpartum and 8 pregnant FSWs in Port Elizabeth. Interview guides were used to probe women's experiences, challenges, and concerns about selling sex during pregnancy and post‐delivery in a high‐HIV‐prevalence context. Interviews were transcribed, translated, and coded using thematic analysis. FSWs experienced and feared violence by clients during pregnancy, highlighting the need for safe work environments. Further, FSWs expressed concerns about HIV acquisition and vertical transmission during the perinatal period. Physical challenges related to pregnancy affected women's ability to work. Returning to work post‐delivery presented barriers to initiating and practicing exclusive breastfeeding. As a result, many FSWs practiced mixed feeding. Interventions, tailored to respond to FSW's challenges and experiences, may offer improved health outcomes in this context.